Stem Education Determines Interdisciplinary Integration (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The abbreviation "STEM" (S – science, T – technology, E – engineering, M – mathematics) for the first time offered American bacteriologist R . Colwell . But STEM began to be actively used in 2011 By initiative biologist Judith Ramali. It is known What at first used abbreviation SMET, and then came STEM. Judith A. Ramali notes that “STEM education is teaching and learning in science, technology, engineering and mathematics.” Germany, as the country that first announced the era of the fourth industrial revolution to the world, is doing a lot to implement STEM technologies in educational institutions. Germany has chosen its own acronym for STEM: MINT. Translated, it means “mathematics, computer science, natural sciences and technology.” The national German MINT portal presents strategic development vectors: digital transformation of schools, digital competences of youth, MINT for girls, MINT technology. Germany ranks one of the first places in preparing STEM graduates. The country is implementing the initiative "MINT Zukunft schaffen" ("creating the MINT future"), within the framework of which all indicators related to the implementation of MINT are measured: competencies, the number of graduates in this area, the percentage of women participants this spheres And that similar. Interesting experience implementation technologies STEM through the active method of constructing technical toys, which is introduced in Vietnamese schools. The main focus of STEM implementation in Vietnam is the idea of developing active cross-curricular learning through the development of technical toys.